Gluconate action in the hydration of calcium aluminate cements: Theoretical study, processing of aqueous suspensions and hydration reactivation. Issue 8 (July 2019) - dos Santos, T.; Pereira, C.I.; Gonçalves, R.; Salvini, V.R.; Zetterström, C.; Wöhrmeyer, C.; Parr, C.; Pandolfelli, V.C.
Abstract: Considering the production of stable CAC aqueous suspensions, this work addressed the action of gluconate anion as a Ca 2+ complexing agent and retarder of CAC hydration. Using quantum simulations, the complexation energy of gluconate complexes was calculated. The pH range of stability for the complexes was estimated and aqueous suspensions containing CAC and sodium gluconate (NaG), stable up to 4 days at room temperature, were prepared. Afterwards, their hydration reactions were reactivated by adjusting the systems' pH. Results of solidification kinetics and mineralogical characterisation highlighted that, after reactivation, calcium aluminate hydrates were formed. Thermodynamics simulations indicated that using NaG up to 1 wt% would not be deleterious to the systems refractoriness up to 1700 °C. These systems could be applied in less explored processing routes for CAC-based refractory compositions ( e.g. slip casting, direct foaming and additive manufacturing), resulting in innovations to produce advanced refractory ceramics.